Load Dividing and Reclustering technique to Improve the Reliability of Data In a Network - Sethi, Sonia; Kumar, Deepak (International Journal of Computer Sciences and Engineering, 2025)
The organizing and scheduling of the network to conserve the energy of the node to accomplish better communication with the sink is the key challenge in a network. The numbers of techniques are established to cluster the network according to the distance of nodes from the sink. This paper presents a technique which allows the cluster to divide its load equally which helps to minimize the data loss. The cluster head selection takes place in two levels according to probability, threshold and its distance from sink. At level 0 cluster head selected will not take part in level 1 cluster head selection and aggregated data at level 0 is forwarded to level 1 cluster head according to their minimum distance concept. The data from cluster heads at level 1 is divided into two equal part so that to minimize the energy consumption and data loss